Dampak Pergantian Menteri Keuangan terhadap Volatilitas Saham Sektor Perbankan di Bursa Efek Indonesia - Ridho Dyan Alvionta; Jhonny Ferlion; Frenly Saputra; Ade Yuniati; Agus Satrya Wibowo (Jurnal Ilmiah Wahana Akuntansi, 2025)
This study analyzes the impact of the change of Minister of Finance on stock volatility on the Indonesia Stock Exchange (IDX) using an event study approach. The event observed was the inauguration of the Minister of Finance on September 8, 2025, with an observation period of seven days before and after. The sample consists of 47 companies in the banking sector selected based on their liquidity and sensitivity to fiscal policy. Analysis using the Wilcoxon Signed Rank Test shows no significant difference between the two periods. These results indicate that the market did not overreact to the change of finance minister and viewed it as part of normal government dynamics. These findings support the semi-strong form efficient market hypothesis, in which public information is quickly absorbed without triggering extreme price fluctuations. The implications of this study show that the banking sector is highly resilient to short-term policy changes and emphasize the importance of fiscal policy credibility and consistency in maintaining investor confidence and information efficiency in the Indonesian capital market.